1996
DOI: 10.1007/bf01441564
|View full text |Cite
|
Sign up to set email alerts
|

Children's responding to live interadult conflict: The role of form of anger expression

Abstract: Children's responses to interadult arguments were examined as a function of three forms of disputes: covert, verbal, and physical. Four- to seven-year-olds' overt-behavioral responses to live enactments of arguments between a male and a female were videotaped and coded for behavioral distress and anger/aggression, and children were then interviewed. Although children exhibited overt-behavioral distress in response to all forms of disputes, physical arguments evoked the highest levels of distress. Some gender d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 49 publications
1
17
1
1
Order By: Relevance
“…Although boys and girls are both likely to see interparental conflict as a threat, boys are more likely to interpret interparental conflict as a threat to themselves, whereas girls are more likely to perceive interparental conflict as a threat to the harmony of family relationships (Grych et al., ). In addition, compared to boys, girls may be more likely to blame themselves for interparental conflicts, feel caught in the middle of conflicts, and feel the need to intervene (El‐Sheikh & Reiter, ). Differences between boys and girls are also evident across different developmental periods.…”
Section: Additional Factors That May Moderate How Interparental Conflmentioning
confidence: 99%
“…Although boys and girls are both likely to see interparental conflict as a threat, boys are more likely to interpret interparental conflict as a threat to themselves, whereas girls are more likely to perceive interparental conflict as a threat to the harmony of family relationships (Grych et al., ). In addition, compared to boys, girls may be more likely to blame themselves for interparental conflicts, feel caught in the middle of conflicts, and feel the need to intervene (El‐Sheikh & Reiter, ). Differences between boys and girls are also evident across different developmental periods.…”
Section: Additional Factors That May Moderate How Interparental Conflmentioning
confidence: 99%
“…Using an analog methodology in which children were exposed to simulated conflict scenarios, Cummings, El-Sheikh, and colleagues have found that children perceive physical interadult conflict as more angering and distressing than verbal marital altercations (e.g., Cummings et al 1989; El-Sheikh and Cheskes 1995; Goeke-Morey et al 2003; Harger and El-Sheikh 2003; Rieter and El-Sheikh 1999). Nevertheless, all forms of marital conflict, including physical, verbal, or covert (e.g., silent treatment) evoke negative affect and distress in children (Cummings et al 2002; El-Sheikh and Reiter 1996 ; Rieter and El-Sheikh 1999 ). For a better understanding of child behavior problems and cognitive and academic performance in the context of family risk, child functioning needs to be examined in the context of both marital verbal/psychological and physical aggression.…”
Section: Marital Violence and Children’s Adjustmentmentioning
confidence: 99%
“…There is a reliable preponderance of evidence indicating a female risk for anxiety symptoms, anxiety disorders, and psychosocial correlates of anxiety, which emerge and become established by school entry (Lewinsohn et al 1998;Silverman et al 2003). There are also marked middle childhood differences between boys and girls in: response to family dysfunction (Jacobvitz et al 2004); in representations of various dyadic family interactions (Bretherton and Page 2004); appraisals of anger expressions in un-related adults (El-Sheikh and Reiter 1996) and interparental conflict (Grych et al 2003); the shielding of children from interparental disputes that turn toward violence, with boys being less shielded and more involved in such domestic interactions (Hess and Camara 1979); the experience of stress, which varies across type and context (Rudolph and Hammen 1999); and the impact of perceptions and characteristics of family relationships on the later development of problem behavior in adolescence (Goldstein et al 2005). Conjugal interactions also vary according to child gender, with mother, father, son, and daughter responses to each other also being mediated by individual levels of marital satisfaction (Kerig et al 1994).…”
mentioning
confidence: 97%